Avaliação do potencial biotecnológico de prospecção do extrato bruto da Ocotea puberula (Rich.) Ness em camundongos - Miyasaki, Isabella Stelle (2021)
Medicinal plants have been used for many years to treat and reduce the symptoms of diseases, so it is important that new research with plants be carried out, aiming to evaluate their medicinal effects, and enabling the production of a phytotherapics. The evaluation of medicinal plants, their compounds and medicinal effects that are popularly known is essential, however, the evaluation of their possible immunomodulatory effects such as stimulation of the production of proinflammatory cytokines and increased activity of certain cells of our immune system is extremely relevant. Ocotea puberula, popularly known as cinnamon-guaicá, cinnamon-parda, cinnamonsebo or as guaicá, is part of the Lauraceae family and is used for dysentery, diarrhea and can be indicated for use in cases of eczema, dermatoses, anti-inflammatory effects, inflammatory, analgesic, antioxidant, and stimulant. This work aims to evaluate the immunomodulatory potential of the crude extract of Ocotea puberula. Hot hydroalcoholic extraction was performed to preserve the alkaloids in the extract. The experimental part consists of a total of 160 male Swiss mice weighing approximately 20g that will be divided into 2 experimental groups, Phase 1 and Phase 2, containing 40 and 120 mice in each group, respectively. Phase 1 will consist of evaluating the production and determination of nitric oxide. Phase 2 consists of the evaluation of hematological and immunological biomarkers in vivo. The data obtained from the analyzes were evaluated through analysis of variance ANOVA followed by the Bonferroni test. The oxide determination, the concentration of 50 ng/mL stood out and was used as the basis for phase 2 of this study. In the analysis of phase 2 hematological biomarkers, it was possible to observe changes in all exposed groups. The main change was a significant increase in neutrophils when compared to the control group. The concentration of nitric oxide in the in vivo experiment showed superior results in all exposed groups and the concentration increased with the time of exposure to the extract. These results indicate that the crude extract of Ocotea puberula has immunomodulatory potential.